MICROHARDNESS AND FLEXURAL STRENGHT OF RESINS FOR THE POSTERIOR SECTOR: IN VITRO STUDY - Becerra-Gutiérrez, Jerica Alejandra (2025)
Introduction. Contemporary resin composites have improved mechanical properties, such as microhardness and flexural strength, to better withstand masticatory loads. Nevertheless, fracture and wear remain common causes of failure in posterior restorations. Objective. To compare the surface microhardness and flexural strength of Filtek™ Z350 XT (3M ESPE), Estelite Posterior (Tokuyama), Beautifil II (Shofu), and Opallis (FGM). Materials and Methods. In vitro study with four resin composites (n = 10 per group). Disc-shaped specimens (5 mm × 2 mm) were used to evaluate Vickers microhardness (VHN), and bar-shaped specimens (25 mm × 2 mm × 2 mm) to perform a three-point bending test using a universal testing machine. Results. For flexural strength, Estelite Posterior showed the highest mean (136.59 ± 9.13 MPa). For surface microhardness, Filtek Z350 XT yielded the highest value (67.99 ± 2.60 VHN). Significant differences were found among groups (p < 0.001), except between Z350 XT and Estelite Posterior for microhardness (p = 0.101) and flexural strength (p = 0.252). Conclusion. Filtek Z350 XT and Estelite Posterior exhibited higher surface microhardness and flexural strength compared with Beautifil II and Opallis. Clinical Relevance. These results support more informed selection of posterior restorative materials, considering performance and longevity in the oral environment prior to clinical use.